Endoscopic Drainage of Giant Pancreatic Pseudocysts Using Both Lumen-Apposing Metal Stent and Plastic Stent: A Report of Two Cases and Review of the Current Literature - Hussam I. A. Alzeerelhouseini; Muawiyah Elqadi; Mohammad N. Elqadi; Sadi A. Abukhalaf; Hazem A. Ashhab (Case Reports in Gastrointestinal Medicine)
Introduction. A pancreatic pseudocyst (PP) with major diameter equal to 10 cm or more is called a giant pseudocyst. The ideal management for giant PPs is controversial. Endoscopic drainage is an alternative nonsurgical approach for PP management. Only a few cases of giant PPs were reported to be managed by endoscopic drainage. Case Presentation. We reported two cases of giant PPs following an episode of acute pancreatitis. Both were resolved following endoscopic cystogastrostomy using metallic and double-pigtail stents with excellent outcomes. There was no history of recurrence or complications on follow-up. In addition, we extensively reviewed all available literature studies of giant pancreatic pseudocyst presentation, management, and complications. We summarized all reported cases and presented them in a comprehensive table. Conclusion. The endoscopic cystogastrostomy approach is cost saving, can avoid surgical complications, and offers an early hospital discharge.